2016
DOI: 10.1186/s13059-016-0957-5
|View full text |Cite|
|
Sign up to set email alerts
|

Single-cell analysis of CD4+ T-cell differentiation reveals three major cell states and progressive acceleration of proliferation

Abstract: BackgroundDifferentiation of lymphocytes is frequently accompanied by cell cycle changes, interplay that is of central importance for immunity but is still incompletely understood. Here, we interrogate and quantitatively model how proliferation is linked to differentiation in CD4+ T cells.ResultsWe perform ex vivo single-cell RNA-sequencing of CD4+ T cells during a mouse model of infection that elicits a type 2 immune response and infer that the differentiated, cytokine-producing cells cycle faster than early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 33 publications
(40 reference statements)
3
53
0
Order By: Relevance
“…We found that cell populations respond to cytokine combinations in a way that is additive in nature, such that the mean response to a combination of cytokines equals the sum of the responses to the individual cytokines. Additive signal integration was observed in other studies of cellular responses (45,(54)(55)(56)(57)(58). We show that, in the case of CD4 + T-cell differentiation, however, there is a hierarchy that modulates the summation of signals: some inputs are more dominant, and if present, they modify the coefficients of the additive model.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We found that cell populations respond to cytokine combinations in a way that is additive in nature, such that the mean response to a combination of cytokines equals the sum of the responses to the individual cytokines. Additive signal integration was observed in other studies of cellular responses (45,(54)(55)(56)(57)(58). We show that, in the case of CD4 + T-cell differentiation, however, there is a hierarchy that modulates the summation of signals: some inputs are more dominant, and if present, they modify the coefficients of the additive model.…”
Section: Discussionmentioning
confidence: 59%
“…Previous models described differentiation of Th cells toward a specific fate (55)(56)(57) or focused on key molecular components (38,(58)(59)(60). Other models describe Th differentiation at a higher level of detail by modeling regulatory networks of increasing complexity (61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…The functional diversity of natural killer T (NKT) cells is difficult to characterize using cytometry alone; however, single cell RNA-seq analysis revealed differential patterns of gene expression that resolve NKT subsets and indicate potential functions [66]. Single cell transcriptomic profiling is also particularly useful for understanding T cell differentiation and proliferation, as the expression of key transcription factors and other regulatory genes can be easily ascertained and used to assign cells to differentiation trajectories [67,68]. …”
Section: High-dimensional Analyses Reveal An Expanded View Of Cd4+ T mentioning
confidence: 99%
“…While these studies profiled cell populations defined by cell surface, cytokine or TF expression, recent single cell genomic studies (6, 43) have increased the resolution at which we characterize cellular populations and their fluidity. For example, Th17 cells were shown to span a continuum of states, from higher expression of a program associated with pathogenic effect to one characteristic of regulatory cells, with distinct regulators for each program (6).…”
Section: Plasticity Of Cell Differentiationmentioning
confidence: 99%